Esensi Pendidikan Islam Bagi Generasi Alpha dalam Perspektif Filsafat Ilmu - Haira Zulfia; Azmi Fitrisia; Ofianto Ofianto (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2022)
This study aims to determine the essence of Islamic education for Generation Alpha. This study also tries to look at the rationalization aspect of Islamic education for the alpha generation in the perspective of the philosophy of science. This research is a library research which will collect data related to the concept of Islamic education for the alpha generation in the perspective of the philosophy of science. The results of this study are Islamic education, alpha generation, the essence of Islamic education for the alpha generation, and the foundation of Islamic education for the alpha generation in the perspective of the philosophy of science.